Current sheet models of solar flares - Priest, E R (Solar physics, 1976)
Current sheets have been suggested as the site for flare energy release because they can convert magnetic energy rapidly into both heat and directed plasma energy. Also, they contain electric fields with the potential of accelerating particles to high energies. The basic properties of current sheets are first reviewed. For instance, magnetic flux may be carried into a current sheet and annihilated. An exact solution for such a process in an infinitely long sheet has been found; it describes the annihilation of fields that are inclined at any angle, not just 180 deg. Moreover, field lines that are expelled from the ends of a current sheet can be described as having been reconnected. The only workable model for fast reconnection in the solar atmosphere, namely Petschek's mechanism, has recently been put on a firm foundation; it gives a reconnection rate that depends upon the electrical conductivity, but is typically a tenth or a hundredth of the Alfven speed. A current sheet may be formed when the sources of an initially potential field begin to move; a simple analytic technique for finding the position and shape of such a sheet in two dimensions now exists. Finally, a sheet with no transverse magnetic field component is subject to the tearing-mode instability, which rapidly produces a series of loops in the field. The main ways in which current sheets have been used for solar flare models is described. Syrovatsky's mechanism relies upon the increase of the electric current density during the formation of a sheet, to a value in excess of the critical value j* for the onset of microinstabilities. But Anzer has recently demonstrated that the critical value is most unlikely to be reached during the initial formation process. Sturrock, on the other hand, has advocated the occurrence of the tearing-mode instability in an open streamer-like configuration (which may result from the eruption of a force-free field). But recent observations do not point to that as the relevant configuration. Rather, they suggest that flares are triggered by the emergence of new magnetic flux from below the solar photosphere. This has led Heyvaerts, Priest, and Rust (1976) to propose a new emerging flux model, according to which, as more and more flux emerges, so reconnection occurs, producing some preflare heating. When the current sheet reaches such a height (around the transition region) that its current density exceeds j*, then the impulsive phase of the flare is triggered. The main phase is caused by an enhanced level of magnetic energy conversion in a turbulent current sheet. The type of flare depends upon the magnetic environment in which the emerging flux finds itself. A surge flare results if the flux appears near a strong unipolar region such as a simple sun spot, whereas a two-ribbon flare may be produced by flux emergence near an active region filament; in which case, the main phase energy is released from the field that surrounds the filament.